Preparation of Intensity Frequency and Duration (IFD) curves for the estimation of droughts in agricultural companies - Brown Manrique, Oscar Nemesio (2012)
The present investigation analyzes the elaboration of the drought curves of "Intensity Frequency Duration" (IFD) in the area of the agricultural enterprise "Juventud Heroica", located in Venezuela municipality, Ciego de Avila province, Cuba. The rainfall data comprise the 28-year precipitation record maintained by the enterprise. The results demonstrate that an appropriate estimate of the maximum intensity of the drought is achieved in function of the duration, through potential models and second and third order polynomials. The Talbot equations provide a correct relationship between the maximum intensity and the duration of the drought  for the periods of 2, 7, 9, 14 and 28 years; however they do not achieve reliable results for periods of 1 and 3 years. Aparicio's model gives an appropriate instantaneous functional relationship among the three analyzed variables of severity, with an appropriate correlation coefficient. In all the cases evaluated, a correct estimate and prediction is assured of the maximum intensity of drought in the study area.